Eksplorasi Literasi Pasar Modal di Kalangan Perempuan - Rosya Luckyta Aji Kusuma; Sarah Apriani; Sri Rachman Silvana Dewi; Dedi Mulyadi (Peneliti.net, 2023)
On the benefits factor, women have not felt the benefits of investing in the capital market. Therefore, to increase capital market literacy among women, it is recommended that the Indonesia Stock Exchange and the Financial Services Authority access information to the public in the form of outreach by collaborating with schools and tertiary institutions as well as conducting outreach through social media by cooperating with capital market influencers. Schools and tertiary institutions can incorporate capital market literacy into the learning curriculum so that all students and students get a complete understanding of the capital market. Choose words that are easily understood by listeners in the delivery of socialization in order to increase listener understanding. Reconsider the number of women in the composition of the capital market outreach team. Starting from the socialization team leader, administrators, and spearheads or influencers who play a role. With the increasing number of women, the opportunities for approaching women to increase capital market literacy can be even better.